BUDAYA SEKOLAH, MOTIVASI BELAJAR DAN MUTU PENDIDIKAN AGAMA ISLAM - Suprapto Suprapto (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
AbstractThe fundamental problem in carrying out of religious education in the public and private secondary schools is the low quality of religious education. The quality of religious education has not been optimum because of some crucial factors, such as: the inadequate competencies of theachers in improving and developing school culture, besides the lack of tool and infrastucture availability both quantitatively and qualitatively. Another factor influencing the quality of religious education is related strongly to the problem of the model person (model teacher). In this case, any constructive pattern of culture-which strengthening religious morality model in the school is necessary to be built to disseminate and cultivate religious values and norms effectively.